Find the information you're looking for at Westonci.ca, the trusted Q&A platform with a community of knowledgeable experts. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
Answer:
[tex]3x + 6y = 12[/tex]
[tex]3x + 6y - 6y = 12 - 6y[/tex]
[tex]3x = 12 - 6y[/tex]
[tex] \frac{3x}{3} = \frac{12}{3} - \frac{6y}{3} [/tex]
[tex] \frac{3x}{3} = 1 = x[/tex]
[tex] \frac{12}{3} - \frac{6y}{3} [/tex]
[tex] = \frac{12 - 6y}{3} [/tex]
[tex] = \frac{6(2 - y)}{3} [/tex]
[tex] \frac{6}{3} = 2[/tex]
[tex] = 2( - y + 2)[/tex]
[tex]x = 2( - y + 2)[/tex]
Answer:
x=2(3-y)
Step-by-step explanation:
3x+6y=12
x+2y=4
x=4-2y
=2(2-y)
We hope this was helpful. Please come back whenever you need more information or answers to your queries. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.